60.5k views
3 votes
A. -11/3

B. -7/3

C. 7/3

D. 11/3

A. -11/3 B. -7/3 C. 7/3 D. 11/3-example-1

1 Answer

4 votes

Answer:


\displaystyle a = (-11)/(3)

General Formulas and Concepts:

Pre-Algebra

Order of Operations: BPEMDAS

  1. Brackets
  2. Parenthesis
  3. Exponents
  4. Multiplication
  5. Division
  6. Addition
  7. Subtraction
  • Left to Right

Equality Properties

  • Multiplication Property of Equality
  • Division Property of Equality
  • Addition Property of Equality
  • Subtraction Property of Equality

Algebra I

  • Exponential Rule [Powering]:
    \displaystyle (b^m)^n = b^(m \cdot n)
  • Exponential Rule [Rewrite]:
    \displaystyle b^(-m) = (1)/(b^m)

Explanation:

Step 1: Define

Identify


\displaystyle 9 = ((1)/(27))^(a + 3)

Step 2: Solve for a

  1. Rewrite:
    \displaystyle 3^2 = ((1)/(27))^(a + 3)
  2. Rewrite:
    \displaystyle 3^2 = ((1)/(3^3))^(a + 3)
  3. Rewrite [Exponential Rule - Rewrite]:
    \displaystyle 3^2 = (3^(-3))^(a + 3)
  4. Exponential Rule [Powering]:
    \displaystyle 3^2 = 3^(-3(a + 3))
  5. Set up:
    \displaystyle 2 = -3(a + 3)
  6. [Division Property of Equality] Divide -3 on both sides:
    \displaystyle (-2)/(3) = a + 3
  7. [Subtraction Property of Equality] Subtract 3 on both sides:
    \displaystyle (-11)/(3) = a
  8. Rewrite:
    \displaystyle a = (-11)/(3)
User Lef
by
6.1k points